2021
DOI: 10.31234/osf.io/5ejwu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 first lockdown as a window into language acquisition: associations between caregiver-child activities and vocabulary gains.

Abstract: The COVID-19 pandemic, and the resulting closure of daycare centers worldwide, led to unprecedented changes in children’s learning environments. This period of increased time at home with caregivers, with limited access to external sources (e.g., daycares) provides a unique opportunity to examine the associations between the caregiver-child activities and children’s language development. The vocabularies of 1742 children aged 8-36 months across 13 countries and 12 languages were evaluated at the beginning and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 24 publications
5
26
0
Order By: Relevance
“…This pattern of overall gains is consistent with recent reports of first and second language learning during the COVID era ( Hopp and Thoma, 2020 ; Kartushina et al, 2021 ). Hopp and Thoma (2020) compared cross-sectional samples of German primary school learners of English: one group experienced 15 weeks of foreign language instruction interruption secondary to COVID-induced school closure and curricular reduction, the other group was assessed the year prior and had continuous English instruction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This pattern of overall gains is consistent with recent reports of first and second language learning during the COVID era ( Hopp and Thoma, 2020 ; Kartushina et al, 2021 ). Hopp and Thoma (2020) compared cross-sectional samples of German primary school learners of English: one group experienced 15 weeks of foreign language instruction interruption secondary to COVID-induced school closure and curricular reduction, the other group was assessed the year prior and had continuous English instruction.…”
Section: Discussionsupporting
confidence: 91%
“…The group that experienced instruction suspension made as much gains in English as the group that had continuous instruction. Kartushina et al (2021) conducted a large-scale multinational study of vocabulary development in monolingual infants and toddlers using various versions of the Communicative Development Inventories ( Fenson et al, 2007 ). They found that children gained more words than expected (based on normative data) during lockdown, a result that could be explained by either the parents’ increased awareness of their children’s vocabulary knowledge or more intense caregiver-child interactions during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of overall gains is consistent with recent reports of first and second language learning during the COVID era (Hopp & Thoma, 2020;Kartushina et al, 2021). Hopp and Thoma (2020) compared cross-sectional samples of German primary school learners of English: one group experienced 15 weeks of foreign language instruction interruption secondary to COVID-induced school closure and curricular reduction, the other group was assessed the year prior and had continuous English instruction.…”
Section: Discussionsupporting
confidence: 83%
“…One hundred (53%) target children were male, 89 female. Vocabulary scores and a similar measure of ECEC attendance at the Spring observation point for most of our sample ( N = 163) are also reported in Kartushina et al (2021), which investigates separate questions on the impact of the home environment on language development.…”
Section: Methodsmentioning
confidence: 55%